A low-cost method for real-time evaluation of median frequency during cyclic contractions - Ho, C. S.; Lin, G. C.; Chen, C. Y.; Cheng, J. L. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The appropriate exercise intensity can be used to improve physical strength as well as to prevent musculoskeletal injuries, and scientific analysis can evaluate the effectiveness of resistance training. The goal of the study was to test a low-cost method for real-time evaluation of median frequency (MDF) during cyclic contractions. Surface electromyography (sEMG) is an objective, non-invasive and pain-free method for assessing and monitoring muscle fatigue in humans performing resistance exercise. In the study, we provided a low-cost method for real-time evaluation of MDF during cyclic contractions. For a well designed program that controls the accumulation of fatigue, local muscle fatigue must be quantified.